Association between HLA alleles and lamotrigine-induced cutaneous adverse drug reactions in Asian populations: A meta-analysis. (August 2018) - Deng, Yilun; Li, Shaoping; Zhang, Lin; Jin, Hou; Zou, Xiaoyi
Highlights: HLA-B*1502 is a risk factor for LTG-induced bullous lesions like SJS/TEN. HLA-A*2402 is associated with the susceptibility to either SJS/TEN or MPE. HLA-A*3303 is a protective allele against LTG induced MPE. Abstract: Purpose: The aim of this study was to assess the association between human leukocyte antigen (HLA) variants and lamotrigine (LTG)-induced cutaneous adverse drug reactions (cARDs). Methods: A comprehensive literature search was conducted on the relationship of HLA alleles with LTG-induced cADRs in Asian populations, through PubMed, Embase, and Cochrane Library. The last search was in February 2018. The pooled odds ratio (OR) with 95% confidence interval (95% CI) was used to access the strength of the association between an HLA allele and LTG-induced cADRs. Results: A total of 11 studies met the inclusion criteria and were enrolled in our meta- analysis, which were based on Chinese, Korean, and Thai populations. Among these populations, we observed that HLA-B*1502 is a risk allele for LTG-induced Stevens-Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) in Chinese populations (pooled OR 2.4, 95% CI: 1.20–4.78, P = 0.01), HLA-A*2402 was found to be a significant risk allele for both SJS/TEN (pooled OR 3.50, 95% CI: 1.61–7.59, P = 0.002) and maculopapular eruption (MPE) (pooled OR 2.14, 95% CI: 1.10–4.16, P = 0.03), and HLA-B*3303 was considered to be a protective marker for MPE in Chinese and Korean populations (pooled OR 0.2, 95% CI 0.06–0.64, P = 0.007). Conclusions: In Asian populations, HLA-B*1502 is a risk factor for LTG-induced bullous lesions such as SJS/TEN in Chinese populations, and HLA-A*2402 is associated with the susceptibility to either SJS/TEN or MPE. HLA-A*3303 is a protective allele against LTG-induced MPE in Chinese and Korean populations.